Case report Basal cell nevus syndrome: a case report and review of literature - Bergler-Czop, Beata; Meszyńska, Elżbieta; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Basal cell nevus syndrome (Gorlin-Goltz syndrome, nevoid basal cell carcinoma syndrome – NBCCS) is an autosomal dominant inherited disorder. We describe a patient with symptoms of NBCCS that fulfilled the diagnostic criteria: more than 2 basal cell carcinoma (BCC) or 1 BCC before the age of 30 years or more than 10 basal cell nevi, 3 or more plantar/palmar or plantar pits, calcification of the cerebral falx, positive family history for basal cell nevus syndrome, congenital skeletal anomalies of the spine and ribs, prominent frontal tubers, cleft palate. Despite the presence of those symptoms that suggested the diagnosis, the patient was not previously informed about the diagnosis of a genetic syndrome and the consequences of such diagnosis especially about the oncological risk, the need of genetic advice before family planning.